Persepsi Masyarakat Islam Kejawen di Kabupaten Cilacap terhadap Implementasi Pasal 7 Ayat 1 Undang-Undang Nomor 16 Tahun 2019 tentang Perubahan Usia Perkawinan - Muchimah, Muchimah; Azizah, Mabaroh (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This article discusses the perceptions of the Javanese Islamic community regarding the implementation of Article 7 Paragraph 1 of Law Number 16 of 2019 concerning changes in the age of marriage. This research originated from a judicial review filed by the Indonesian Child Protection Commission (KPAI), the Constitutional Court. The decision decided that Article 7 paragraph (1) is as long as the phrase "16 years". The Marriage Law is considered to be contrary to the 1945 Constitution (UUD) of the Republic of Indonesia (NKRI) and does not have binding legal force. Finally, the Constitutional Court finally granted a judicial review of Article 7 paragraph 1, this was because Article 7 Paragraph 1 was discriminatory and not in accordance with Article 27 Paragraph (1) of the 1945 Republic of Indonesia Constitution concerning equal rights before the law and the Child Protection Law which stated that boys -Men and girls have the same rights. The aim of this research is to determine the implementation of Article 7 Paragraph 1 of the 1974 Marriage Law in the Indigenous Anak Putu (ATAP) community in Cilacap Regency. The results of this research indicate that the implementation of Article 7 Paragraph 1 of Law Number 16 of 2019 concerning Marriage in the Kejawen Islamic Community in Cilacap Regency has been carried out as it should. Evidenced by the existence of a long process before the occurrence of the marriage contract. Apart from the procession, there are traditional rules that must not be abandoned, the Anak Putu Traditional Community also upholds the laws and norms that apply in Indonesia. So that in carrying out customary rules it is not intended to violate or get rid of state regulations. However, this is where the customary rules of the Anak Putu Tradition are carried out in tandem with state law. Keywords: Community Perception, Kejawen Islam, Changes in Age of Marriage